2012
DOI: 10.7314/apjcp.2012.13.9.4707
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Annexin A1 Expression in Pancreatic Ductal Adenocarcinoma

Abstract: Annexin A1 is a 37-kDa calcium-and phospholipid-binding protein of the annexin superfamily considered to play an important role in tumorigenesis. However, associations with clinicopathological features in pancreatic ductal adenocarcinoma (PDAC) cases have yet to be fully defined. We therefore investigated the prognostic value of annexin A1 protein as a PDAC biomarker in 83 tumor and matched non-cancerous tissues or normal pancreas tissues. Expression was analyzed using real-time RT-PCR, Western blotting and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…ANXA1 protein can perform numerous functions in cancer acting as either a tumour suppressor or an oncogene, depending on the cancer type 36 37 38 39 . In tissues from patients with PC, ANXA1 protein is over-expressed and has been correlated with poor differentiation and prognosis 5 6 although its role in the PC malignant transformation remains inadequately defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANXA1 protein can perform numerous functions in cancer acting as either a tumour suppressor or an oncogene, depending on the cancer type 36 37 38 39 . In tissues from patients with PC, ANXA1 protein is over-expressed and has been correlated with poor differentiation and prognosis 5 6 although its role in the PC malignant transformation remains inadequately defined.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous disturbances of biological pathways have been found in PC insurgence leading to tumour development and progression. Comparisons of protein profiles between PC and normal pancreas highlighted several proteomic alterations including the over-expression of annexin A1 (ANXA1) protein 4 5 6 .…”
mentioning
confidence: 99%
“…In PC there is an abnormally high expression of a number of important tyrosine kinase growth factors and receptors, like the Epidermal Growth Factor (EGF) family, which may contribute to the neoplasia growth by autocrine and paracrine effects [ 40 , 41 ]. Immunohistochemistry studies showed that EGF Receptor (EGFR) over-expression positively correlates with advanced tumour staging and lymph node metastasis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have revealed that partial molecules enjoy close relationships with cancer emergence and development, as well as drug resistance (Gerke et al, 2005;Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%